Comparison analysis of VNA residual errors estimation algorithms with time domain separation - Savin, Aleksandr A.; Guba, Vladimir G.; Bykova, Olesia N. (2015 86th ARFTG Microwave Measurement Conference, 2015)
In the paper results of algorithms' comparison which are utilized for determination of vector network analyzer (VNA) residual parameters are described. Separation of parameters in time domain is the basis for the algorithms. The algorithms based on unscented Kalman filter, least mean square technique and conventional time domain filtering are reviewed. Experimental results are achieved in coplanar waveguide environment in frequency range up to 70 GHz using two precision lines with different lengths.